2021
DOI: 10.1177/1557988320982184
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health-Related Quality of Life Among Survivors of Testicular Cancer: A Systematic Review

Abstract: This study aimed to determine if the current health-related quality of life (HRQoL) tools created for survivors of testicular cancer are collecting the highest quality of data via a two-step methodological critique of both the seminal studies that produced a survivor of testicular cancer HRQoL tool (Phase 1) and the actual tool itself (Phase 2). It is the goal of this current article to present and discuss Phase 1. A systematic review aimed to assess the methodological quality of studies conducted to create i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For both appraisal tools, a study was assessed to be (1) good quality if its score was equal to or exceeded 70% of the total, (2) fair quality if the score was between 60% and 69.9%, and (3) low quality if the score was below 60%. 41 S.P. performed the critical appraisal of the included studies and F.R.…”
Section: Critical Appraisal Of Included Studiesmentioning
confidence: 99%
“…For both appraisal tools, a study was assessed to be (1) good quality if its score was equal to or exceeded 70% of the total, (2) fair quality if the score was between 60% and 69.9%, and (3) low quality if the score was below 60%. 41 S.P. performed the critical appraisal of the included studies and F.R.…”
Section: Critical Appraisal Of Included Studiesmentioning
confidence: 99%
“…In the literature, the findings are varied between erectile dysfunction, age and marital status for men with testicular cancer [16]. The study results reported that older age could be factor on sexual interest and satisfaction with sex life, which has negatively associated with health-related quality of life [17]. In addition, having a partner has positive impact on sexual function for me diagnosed with testicular cancer [8,18].…”
Section: Discussionmentioning
confidence: 99%
“…Erectile function 6, orgasm function 2, sexual desire 2, sexual satisfaction 3 and general satisfaction are questioned with 2 questions. This form questions the quality of erectile function during the last 4 weeks [17]. The answers given to the questions asked were scored between 0 and 5 in this form.…”
Section: -Item International Index Of Erectile Function (Iief-5)mentioning
confidence: 99%
“…Beyond this direct relationship between side effects and QoL, there is concern that current QoL assessments lack the sensitivity to capture the complexity of QoL sequelae experienced by TCS. 116,118,119 Most TCS are diagnosed and treated during a life stage critical to the development of their autonomy and self-concept; 120 however, most studies to date report on older TCS with few studies explicating the adolescent and young adult TCS experience. 121 Having a stronger understanding of how TC may impede optimal progression through this critical life stage is imperative to mitigating potential long-term negative QoL effects.…”
Section: Quality Of Lifementioning
confidence: 99%